Acute pancreatitis in peritoneal dialysis and haemodialysis: risk, clinical course, outcome, and possible aetiology. Issue 3 (1st March 2000) - Bruno, M J; van Westerloo, D J; van Dorp, W T; Dekker, W; Ferwerda, J; Tytgat, G N J; Schut, N H
Abstract : BACKGROUND: It has been suggested that the incidence of acute pancreatitis in patients with end stage renal failure is increased. AIMS: To assess the risk of acute pancreatitis in patients on long term peritoneal dialysis and long term haemodialysis compared with the general population, to evaluate its clinical course and outcome, and to identify possible aetiological factors. PATIENTS: All patients who were maintained on long term peritoneal dialysis and/or haemodialysis (total dialysis time more than six weeks) from January 1989 to March 1998 in a large general hospital in The Netherlands. METHODS: Retrospective cohort study. Standardised ratios (as an approximate relative risk) between the incidence of acute pancreatitis in haemodialysis or peritoneal dialysis and the general population were calculated. Possible risk factors were identified. Patients with and without acute pancreatitis were compared. RESULTS: In 269 patients on haemodialysis (total of 614 person years), one patient developed an attack of acute pancreatitis. Patients on haemodialysis did not show an increased risk for acute pancreatitis compared with the general population (standardised ratio 11; 95% confidence interval (CI) 0.275 to 60.5). In 128 patients on peritoneal dialysis (total of 241 person years), seven patients had nine attacks of acute pancreatitis. Patients on peritoneal dialysis had a significantly and highly increased risk for acute pancreatitis (standardised ratio 249; 95% CI 114 to 473). Mortality in this series of nine attacks was 11%. No single aetiological risk factor could be identified. CONCLUSIONS: The risk of acute pancreatitis in patients on long term peritoneal dialysis is significantly and highly increased compared with the general population. The underlying causal mechanisms remain to be elucidated.